LOWER BUFFET PRICES LEAD TO LESS TASTE SATISFACTION - (:unkn) unknown (WILEY, 2014)
A field experiment was conducted to assess how diners' taste evaluations change based on how much they paid for an all-you-can-eat (AYCE) buffet. Diners at an AYCE restaurant were either charged $4 or $8 for an Italian lunch buffet. Their taste evaluation of each piece of pizza consumed was taken along with other measures of behavior and self-perceptions. Their ratings were analyzed using 2x3 mixed design analysis of variance (ANOVA). Diners who paid $4 for their buffet rated their initial piece of pizza as less tasty, less satisfactory and less enjoyable. A downward trend was exhibited for each of these measures with each additional piece (P=0.02). Those who paid $8 did not experience the same decrement in taste, satisfaction and enjoyment. Paying less for an AYCE experience may face the unintended consequence of food that is both less enjoyable and rapidly declining in taste and enjoyability. In a sense, AYCE customers get what they pay for. Practical ApplicationsThis study demonstrates that when eating in a less expensive all-you-can-eat (AYCE) buffet, people find the food less tasty. Such a consequence means a less enjoyable experience for the consumers, which may have implications for repeat purchase. By employing a low-price strategy, AYCE restaurants can attract the initial business of customers. However, these customers may end up evaluating the food unfavorably. As a result, the low-price strategy may not be as profitable in the long term. This study has implications for both consumers and restaurants.
Keywords: QUALITY RELATIONSHIP; PERCEIVED QUALITY; MARKETING ACTIONS; FOOD; PRODUCT; FLAVOR; INFORMATION; JUDGMENTS; KNOWLEDGE; INCREASE